Response of FDG avid pelvic bone marrow to concurrent chemoradiation for anal cancer. (February 2020) - Robinson, Maxwell; Muirhead, Rebecca; Jacobs, Clare; Cooke, Rosie; Chu, Kwun-Ye; Van den Heuvel, Frank; Ng, Stasya; Virdee, Pradeep; Strauss, Victoria; Hawkins, Maria
Highlights: Chemoradiation suppression of active bone marrow shown in on-treatment FDG-PET. No suppression shown in un-irradiation bone marrow. Volumes of active bone marrow receiving 20 Gy are associated with blood count nadirs. Abstract: Background and purpose: To determine if suppression of active bone marrow, as defined on FDG PETCT, is seen in on-treatment imaging of anal cancer patients receiving concurrent chemoradiation. Methods and materials: Scans from 26 patients participating in the ART trial (full title: Anal squamous cell carcinoma: Investigation of functional imaging during chemoRadioTherapy), a single center observational study with FDG PETCT prior to radiotherapy and at fraction 8–10 of concurrent chemoradiation were analysed. Active bone marrow was contoured in both the pelvis and un-irradiated thoracic spine. SUV and volume of active bone marrow after 8–10 fractions of treatment were compared to baseline. Dose metrics to pelvic active bone marrow were extracted and compared to reduction in SUV/active bone marrow volume and to blood count nadir using linear regression. Results: Suppression of active bone marrow is seen in the pelvis by a reduction in mean SUV and volume of active bone marrow after 8–10 fractions of treatment. Suppression is not seen in un-irradiated thoracic spine. Dose metrics were associated with reduced SUV and reduced volume of active bone marrow. Volume of active bone marrow receiving <20 Gy was associated with WCC/ANC nadir. 20 Gy was identified as the most likely clinically meaningful dose threshold for toxicity. Volume of active bone marrow receiving <20 Gy correlated to WCC and ANC with an increase of 100 cc being associated with an increase of 0.4 and 0.3 respectively. Conclusion: The effect of concurrent chemoradiation in suppression of active bone marrow is seen in on-treatment FDG PETCT scans. Chemotherapy appears well tolerated after 2 weeks of treatment.